Tricks Ed McBain - McBain, Ed (Arbor House, 1987)
On Halloween night in the 87th Precinct, a liquor store owner is shot by costumed children, a headless torso is discovered, and Detective First Class Eileen Burke, disguised as a hooker, hopes to trap a serial killer
Keywords: Police Procedurals; American Literature